(untitled) (Research, Society and Development, 2021)
Objective: To identify the levels of depression during the pandemic of the Coronavirus COVID-19 and to track the impact of social detachment and / or not during the period of the pandemic related to the signs of depression. Methodology: This is an exploratory study with an approach with a quantitative approach developed during the period from August to December 2020 with a population of 104 participants, including undergraduate students and health professionals, aged between 16 and 50 years old. Three variables were used: sex, age, marital status, being analyzed for the level and predominance of Depressive Disorder developed during social isolation. Data collection using the adaptation of the Questionnaire Patient Health Questionnaire-9 (PHQ-9), validated for Brazil. Results: Females presented Moderate Depressive Disorder (16%), followed by Moderately Severe (11.5 %) on the other hand (12.5%) did not present any disorders. The male gender, on the other hand, presented Moderate Depressive Disorder (12.5%). The age with the highest number of cases was 21 to 30 years, with Moderate Depressive Disorder (18.3%), Moderately severe Depressive Disorder (15%). As for the activities developed during social isolation, most responded: playing with their children, watching series, writing articles, among others. Regarding the feelings of study participants developed in coping with the pandemic, participants could choose more than one option, namely: insecurity, overloaded, sad, stressed, fear, among others. Conclusion: There was a high frequency of feelings of isolation, anxiety and sadness, fear, stress during the study period, as well as depressive disorders in the population.